The Evaluation Of Natural And Anthropic Hazards On The Stability Of The Hydrosalt Complex In Costiui, Romania - S. Zaharia (Society for Mining, Metallurgy & Exploration, 2008)
The authors present the state-of-the-art regarding natural and anthropic hazards on the stability of the saliferous Costiui basin. The factors that may potentially result in sliding, piping and collapse, are emphasized, given the existence of a large number of old salt mines. Also, a geotechnical risk map of this hydrosalt complex in Romania is presented.